Analysis of Child Development in the Home Schooling Learning Process from an Islamic Boarding School Perspective - Nakhma’Ussolikhah Nakhma’Ussolikhah; Muhammad Iqbal Al Ghazali; Mohamad Mizan Sya'roni (Action Research Journal Indonesia (ARJI), 2023)
Early childhood individual development has a major role in the growth and development of children with potential and capacity faster than teenagers (adults). The mistakes made by parents and educators in responding to children's developmental stimuli cannot yet be done in a responsive and measurable manner. Children are still seen as weak individuals and do not have the authority to freely express their creativity and potential. Islamic boarding school education can help children develop optimally in terms of the essence of children's diversity attitudes. The aim of this research is to increase the understanding and skills of parents and educators regarding the function of child development. The aim of this research is to analyze children's development in the home schooling learning process from an Islamic boarding school perspective. Research methodology with a descriptive qualitative approach. The main subjects were 3 children aged 6-9 years and the supporting subjects were 1 parent and 1 Islamic boarding school caregiver . The data collection instrument in this research used interviews . The research results describe that an individual's life starts better by providing positive stimulus to children through learning in the home environment and Islamic boarding school. The definition of school is actually in the home environment. The concept of home schooling was developed for children from an early age to adulthood. Children know home as school at all times. The perception of home schooling is that it is an element of an informal educational institution with a flexible curriculum according to children's needs. Parental education in the 5.0 era is improved to optimize the talents and interests of children's potential at home in continuity